A teaching programme on adverse effects of some selected drugs among college students in selected college at Bhubaneswar, Odisha - Pradhan, Renubala; Behera, Sonia; Kumari Devi, Sinmayee (International Journal of Nursing Research, 2023)
An adverse effect is a harmful and undesired effect resulting from a medication. Adverse effects may cause a reversible or irreversible change, including an increase or decrease in the susceptibility of the individual to other chemicals, foods or procedures. Aim: To assess the knowledge of students regarding adverse effects of self medication of some selected drugs. To evaluate the effectiveness of a Structured Teaching Programme (STP) on adverse effect of self medication of some selected drugs. To compare the pre &post test knowledge score with their selected demographic variables. Method: The study was conducted by using close ended multiple choice questionnaires and the medium of teaching was through Structured Teaching Programme. Results: The level of knowledge of the students reveals that in pretest 65% of the students had poor knowledge and 35% students had average knowledge. But in post test 15% of the students had good knowledge and 85% of students had excellent knowledge. Area wise post test highest mean percentage is 76.4% with mean score (4.58) for area adverse effect of paracetamol. The lowest mean percentage in post test is 73.3% with mean score (2.93) for area “Adverse effect of Antibiotics”. Further effectiveness varies from 58% to 68%. Conclusion: Item wise comparison shows that there is effectiveness of STP in increasing knowledge of the college students on adverse effect of self medication. No significant association was found between knowledge score by the pre &post test group with their selected demographic variable.